Accessing care in multidisciplinary pain treatment facilities continues to be a challenge in Canada. Issue 12 (6th October 2020) - Choinière, Manon; Peng, Philip; Gilron, Ian; Buckley, Norman; Williamson, Owen; Janelle-Montcalm, Audree; Baerg, Krista; Boulanger, Aline; Di Renna, Tania; Finley, Gordon Allen; Intrater, Howard; Lau, Brenda; et al.
Abstract : Background: Multidisciplinary pain treatment facilities (MPTFs) are considered the optimal settings for the management of chronic pain (CP). This study aimed (1) to determine the distribution of MPTFs across Canada, (2) to document time to access and types of services, and (3) to compare the results to those obtained in 2005–2006. Methods: This cross-sectional study used the same MPTF definition as in 2005–2006—that is, a clinic staffed with professionals from a minimum of three different disciplines (including at least one medical specialty) and whose services were integrated within the facility. A comprehensive search strategy was used to identify existing MPTFs across Canada. Administrative leads at each MPTF were invited to complete an online questionnaire regarding their facilities. Results: Questionnaires were completed by 104 MPTFs (response rate 79.4%). Few changes were observed in the distribution of MPTFs across Canada compared with 12 years ago. Most (91.3%) are concentrated in large urban cities. Prince Edward Island and the Territories still lack MPTFs. The number of pediatric-only MPTFs has nearly doubled but remains small (n=9). The median wait time for a first appointment in publicly funded MPTFs is about the same as 12 years ago (5.5 vs 6 months). Small but positive changes were also observed. Conclusion: Accessibility to public MPTFs continues to be limited in Canada, resulting in lengthy wait times for a first appointment. Community-based MPTFs and virtual care initiatives to distribute pain services into regional and remote communities are needed to provide patients with CP with optimal care.